Political economy of redistribution between traditional and modern families - Volker Meier; Matthew D. Rablen (International Tax and Public Finance, 2023)
We analyse a model in which families may either be `traditional' single-earner that care for the child at home or be ` modern' double-earner households that use market child care. Family policies may favour one or the other group, like market care subsidies vs. cash-for-care. Policies are determined by probabilistic voting, where distributional impacts matter, both within and across groups. A higher share of modern households—which can be induced by changes in social norms or by changes in gender wage inequality—may have non-monotone effects, with lower net subsidies to traditional households when their share is very low or very high, and higher subsidies in some intermediate stage. This may explain the implementation of cash-for-care policies and their subsequent tightening in late stages of development, when most voters come from modern households, observed in Norway and Sweden.
Keywords: D13; H21; J13; J18; J22; 340; Redistribution; Child care; Cash-for-care; Subsidies; Family policy; Probabilistic voting